Handbook of Mobile Middleware, The - Bellavista, Paolo (CRC Press, 2009)
Device miniaturization, wireless computing, and mobile communication are driving ubiquitous, pervasive, and transparent computing. Supporting these rapidly evolving technologies requires middleware solutions that address connectivity-level, location-dependent, and context-dependent issues.